Employee Service Performance In Improving The Quality Of The Binjai Medan Urban Village Office - Lidya Lidya; Yenni Samri Juliati Nasution (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2023)
The purpose of this study was to describe the work done by employees of the Head of the Office and to determine the level of public opinion on the quality of services provided to the community in Binjai Village, Medan Denai District. The time frame of this research is from January 16 to February 16, 2023. The data analysis technique used is qualitative data analysis which includes identifying problems with research and providing relevant explanations. Primary data is a technique used for data collection and consists of hash from interviews, observations, questionnaires, and second-order data. It is collected through literature review and review of official documents related to the empirical research problem. The results of the study of five indicators related to employment and the quality of public services in Binjai urban village, medan denai sub-district include tangible goods (evidence), reliability, and quality of life.